Operatings parameters for deployment of a recycler of civil construction residues - Cristo, Aline Fátima Iensen de; Paula, Marciéli Freitas de; Rossato, Marivane Vestena; Zancan, Flávia; Kesseler, Nilmar Sandro; Piccinin, Yvelise Giacomello (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2015)
The Civil construction develops rapidly and with it appears the impacts occasioned by the inadequate allocation of the residues from of this activity, the environment and society. The recycling appears as an alternative to mitigate such impacts. In this regard, this exploratory and descriptive study sought to develop operational parameters for the installation of a recycling of civil construction residues. These were elaborated from a lifting conducted with the company GR2 – Residues Management Ltda, for the purpose of acquiring knowledge about the activities, legal, operational, information for its proper functioning. It was found that the parameters that meet the problems of work, from the proposed objectives are: physical structure for implementation of the project; machinery, equipment and vehicles; raw material; licensing; administrative expenses; fuel costs; electricity consumption of the equipment in the productive process; and workmanship.